Pengaruh Pemberian Pupuk Organik dan NPK Mutiara Terhadap Pertumbuhan Dan Produksi Bawang Merah (Allium Ascalonicum L.) - Davit Iyositomi Sijabat; Seringena Karo; Donatus Dahang (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2021)
The aim of the study was to determine the effect of organic and inorganic fertilizer application on the growth and production of the Batu ijo variety shallots. This research was conducted on the land of UPT Seed Parent Horticulture Kutagadung Berastagi, Berastagi District, Karo Regency, North Sumatra, from June-August 2019. The study used a Factorial Randomized Block Design (RAK) method which consisted of two treatment factors, the first was the dose of Source Organic fertilizer. Sustainable Nature“O” 4 levels: (O0) control, (O1) 270 grams/plot, (O2) 540 grams/plot and (O3) 810 grams/plot. Second, the dose of NPK Mutiara fertilizer with the symbol M consisting of 4 levels: (M0) control, (M1) 44 grams/plot, (M2) 87 grams/plot and (M3) 130 grams/plot, in order to obtain 16 treatment combinations and 2 blocks. The data from the observations were then analyzed for variance with the F test at 5% level and the DMRT test. The results showed that the treatment with Sumber Lestari Alam organic fertilizer had a significant effect on plant height/sample (cm), number of leaves/sample (cloves), number of tillers/sample (stem), number of tubers/sample (cloves), tuber diameter/sample. (mm), and crop production/sample (grams). The treatment of NPK Mutiara fertilizer had no significant effect on the parameters of plant height/sample (cm), number of leaves/sample (cloves), number of tillers/sample (stems), number of tubers/sample (cloves), diameter of tubers/sample (mm), and crop production/sample (grams).